2017
DOI: 10.20853/31-2-1340
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogy of peers: Cultivating writing retreats as communities of academic writing practice

Abstract: Pressure related to research publication output continues, heightened by growing numbers of early career academics. Writing retreats, designed around the pedagogy of community of practice, have potential to initiate early career academics into core academic practices including peer review, and draw them into the community of 'academics as writers'. However, a series of four semi-structured writing retreats based on this pedagogy revealed that supporting novice writers' trajectory of progress from peripheral th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…Retreating provides a way to disconnect from regular commitments with the specific purpose of thinking and writing. Literature on academic writing retreats focusses on a particular way of retreating in a group around a programme that is designed to enable people to write on their own in a group setting (Benvenuti, 2017;Grant, 2006;Jackson, 2009;Kent et al, 2017;Kornhaber et al, 2016;Moore, 2003;Moore, Murphy and Murray;2010;Murray 2015;Murray and Newton, 2009;Papen, and Thériault, 2018;Southwood, 2017;Swaggerty et al, 2011). Retreating together enables support, discussion and shared reflection offering an immersive experience, "affording conducive environments for academic engagement with writing" (Southwood, 2017: 17).…”
Section: Writing Retreats and Academic Wellbeingmentioning
confidence: 99%
See 4 more Smart Citations
“…Retreating provides a way to disconnect from regular commitments with the specific purpose of thinking and writing. Literature on academic writing retreats focusses on a particular way of retreating in a group around a programme that is designed to enable people to write on their own in a group setting (Benvenuti, 2017;Grant, 2006;Jackson, 2009;Kent et al, 2017;Kornhaber et al, 2016;Moore, 2003;Moore, Murphy and Murray;2010;Murray 2015;Murray and Newton, 2009;Papen, and Thériault, 2018;Southwood, 2017;Swaggerty et al, 2011). Retreating together enables support, discussion and shared reflection offering an immersive experience, "affording conducive environments for academic engagement with writing" (Southwood, 2017: 17).…”
Section: Writing Retreats and Academic Wellbeingmentioning
confidence: 99%
“…Jackson ( 2009) Moore ( 2003) and Southwood (2017) discuss the importance of healthy and relaxing activities such as yoga and walking. Social eating is commonly mentioned (including Benvenuti, 2017;Jackson, 2009;Southwood, 2017;and Swaggerty et al, 2011) and the value of pleasant physical environments are identified by Grant (2006), Kent et al (2017), Moore (2003), Murray and Newton (2009), and Southwood (2017). These papers do not explicitly discuss the wellbeing literature but notions of personal, subjective and relational wellbeing are apparent.…”
Section: Writing Retreats and Academic Wellbeingmentioning
confidence: 99%
See 3 more Smart Citations